A suspected case of hepatogenous chronic copper toxicity in a Charolais heifer. Issue 1 (4th January 2016) - Newcomer, Benjamin W.; Wolfe, Dwight; Chamorro, Manuel; Passler, Thomas; Joiner, Kellye
Abstract : A six‐month‐old, orphaned Charolais heifer presented for a five‐day‐history of lethargy and inappetence. On examination, the calf was severely icteric and exhibited haemoconcentration and methaemoglobinaemia. The heifer developed haemolysis and haemoglobinuria the following day leading to the performance of a whole blood transfusion. Liver biopsy revealed evidence of a plant‐based toxic hepatopathy and an elevated copper concentration. Analysis of the calf's feedstuffs did not reveal the source of the excess copper, although one milk replacer sample was above recommended levels for preruminants. No history of access to exogenous copper sources was reported. Hepatogenous chronic copper toxicity results after ingestion of hepatotoxic plants leading to an increase in hepatocyte affinity for copper. A suspected diagnosis of hepatogenous chronic copper toxicity was made. This case demonstrates the disease can be a diagnostic challenge and should be included on the differential list for patients exhibiting methemoglobinaemia and/or signs of liver disease.